Multiple renal angiomyolipomas with asymptomatic nontraumatic pulmonary fat embolus: A case report - Hourieh Soleimani; Masoud Pezeshki Rad; Donya Farrokh; Ehsan Hassannejad; Asma Payandeh; Sepideh Zahedi; Neda Karimabadi (Clinical Case Reports, 2024)
Key Clinical Message Although retroperitoneal bleeding and massive hematuria are potential complications of angiomyolipoma (AML), the pulmonary embolism as a presenting symptom is extremely rare. It is important to be aware that benign AMLs can present with pulmonary fat embolism.